Influencia del estilo directivo en la comunicación interna de las organizaciones. Una aplicación a las agencias de publicidad (2014)
The article is based on the assumption that how an organization is managed entails a specific form of communication. If so, identifying management style can be an indication of how a manger will behave in terms of communication. A model of associations between management style and internal communication is formulated for that purpose. Five style prototypes are identified based on a theoretical analysis. They are: laissez-faire, task-oriented, relationship-oriented, leadership and charismatic leadership. Modes of communication particular to each of these styles are defined. In the second part of the article, the model is tested on a sample of Spanish advertising agencies.